Energy Transition and Its Implications for the Structure of the National Economy - Loso Judijanto; Farkhatun Zaidah (PT. Anagata Sembagi Education, 2026)
Energy transition has emerged as a central global agenda in response to climate change, decarbonization commitments, and sustainable development objectives. In fossil fuel–dependent economies, energy transition entails not only technological change but also profound structural transformations within the national economy. This study employs a qualitative descriptive–analytical approach grounded in political economy and public policy analysis to examine the implications of energy transition for national economic structures. Drawing on policy documents, academic literature, and institutional reports, the study analyzes how energy transition reshapes sectoral composition, labor markets, value distribution, and governance dynamics. The findings indicate that energy transition alters existing economic hierarchies, redistributes power among actors, and creates both opportunities for sustainable growth and risks of socio-economic disruption. The study argues that effective energy transition requires policy frameworks that integrate economic restructuring, social justice, and institutional coordination. It concludes that energy transition should be treated as a comprehensive structural economic policy to ensure equitable and sustainable national development.